Nutrient Intake Profile Among Children Aged 6–24 Months in Indonesia: A Descriptive Analysis - Nurdina, Nazlah; Chandra, Dian Novita; Mudjihartini, Ninik; Sekartini, Rini (World Nutrition Journal, 2025)
Background: Adequate nutrient intake in early childhood is critical for growth, cognitive development, and immune function. The first two years of life are a sensitive period where nutritional deficiencies may lead to long-term consequences. However, many children in low- and middle-income countries fail to meet dietary needs due to limited diversity and poor feeding practices. Objectives: To describe the intake of energy, macronutrients, and key micronutrients among Indonesian children aged 6–24 months